Pediatric dermatology: nosological and consultations profile in a hospital complex in southern Brazil - Iago G. Ferreira; Ana E. Kiszewski-Bau; Magda B. Weber; Lucas A. Bulcão; Camila S. Almeida; Renan R. Bonamigo (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Objective: The study aimed to analyze the profile of dermatoses and Dermatology consultations in a pediatric hospital in southern Brazil. Method: This descriptive and quantitative study was conducted from the analysis of admissions, hospital referrals, and dermatology consultations of pediatric inpatients from August 2018 to January 2020. The researchers performed an investigation in three phases: analysis of pediatric hospitalizations with dermatological diagnosis (phase 1), analysis of dermatology consultations referrals (phase 2), and analysis of dermatology consultations (phase 3). Results: Throughout the 18-month period analyzed, the authors identified 12,656 pediatric hospitalizations, 266 hospital referrals, and 167 dermatology consultations. Hospital dermatoses evidenced a prevalence of 6.8%, with "cellulitis" (L03) and "abscess" (L02) as the main conditions. In dermatology consultations, "dermatitis and eczema" and "skin infections" were the main groups of cutaneous disorders, whereas "atopic dermatitis" (L20) and "drug eruptions" (L27) were the main skin diseases. Corticoids, moisturizers, and antibiotics were the most recommended therapies by dermatologists. Conclusion: From this study, authors evidenced the prominence of inflammatory and infectious cutaneous conditions in children and adolescent populations. Moreover, vulnerabilities and shortcomings of the dermatology consultations process were also found, indicating the need for evaluations and enhancements, mainly regarding clinical data of referrals.